CO-CURRICULAR ACTIVITIES AND SCIENCE ACHIEVEMENT OF SECONDARY SCHOOL STUDENTS - Sharma, Manika; Khatoon, Tahira (THE PRIMARY TEACHER, 2011)
The study was conducted to determine whether participating in sports, computer and internet related activities had any impact on students’ achievement in science of secondary school students. The participating students (N=1500) were selected from urban and rural areas of two districts of western Uttar Pradesh. The t-test was applied to see the significant difference between the science achievement scores of different groups of students. Results indicate that the students involved in different activities yielded better science performance. Therefore, it was concluded that co-curricular activities affect academic performance in science.